A comparative analysis of rainfed and irrigated agricultural production in Ethiopia - Makombe, Godswill; Kelemework, D.; Aredo, D. (2007)
Ethiopia's economy is dependent on agriculture which contributes more than 50% to GDP, about 60% to foreign exchange earning and provides livelihood to more than 85% of the population. Ethiopia has a large potential of water resources that could be developed for irrigation. Despite the large water resources, Ethiopia continues to receive food aid to about 10% of the population who are at risk annually, out of a total of more than 67 million. The government of Ethiopia is committed to solving this paradox through an agricultural led development program that includes irrigation development as one of the strategies. This paper compares rainfed and irrigated agricultural production in Ethiopia. Using the stochastic production frontier approach, the study concludes that irrigation development in Ethiopia is a viable development strategy but attention needs to be paid to improving the technology available to farmers under both rainfed and irrigated production.